Acute Hospital Mortality of Venous Thromboembolism in Patients With Cancer From Registry Data - Yuichiro Okushi; Kenya Kusunose; Yoshihiro Okayama; Robert Zheng; Michikazu Nakai; Yoko Sumita; Takayuki Ise; Takeshi Tobiume; Koji Yamaguchi; Shusuke Yagi; Daiju Fukuda; Hirotsugu Yamada; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background The prognosis of patients with cancer‐venous thromboembolism (VTE) is not well known because of a lack of registry data. Moreover, there is also no knowledge on how specific types are related to prognosis. We sought to evaluate the clinical characteristics and outcomes of patients with cancer‐associated VTE, compared with a matched cohort without cancer using real‐world registry data of VTE. Methods and Results This study was based on the Diagnosis Procedure Combination database in the JROAD‐DPC (Japanese Registry of All Cardiac and Vascular Diseases and the Diagnosis Procedure Combination). Of 5 106 151 total patients included in JROAD‐DPC, we identified 49 580 patients who were first hospitalized with VTE from April 2012 to March 2017. Propensity score was estimated with a logistic regression model, with cancer as the dependent variable and 18 clinically relevant covariates. After propensity matching, there were 25 148 patients with VTE with or without cancer. On propensity score‐matched analysis with 25 148 patients with VTE, patients with cancer had higher total in‐hospital mortality within 7 days (1.3% versus 1.1%, odds ratio [OR], 1.66; 95% CI, 1.31–2.11; P<0.0001), 14 days (2.5% versus 1.5%, OR, 2.07; 95% CI, 1.72–2.49; P<0.0001), and 30 days (4.8% versus 2.0%, OR, 2.85; 95% CI, 2.45–3.31; P<0.0001). On analysis for each type of cancer, in‐hospital mortality in 11 types of cancer was significantly high, especially pancreas (OR, 12.96; 95% CI, 6.41–26.20), biliary tract (OR, 8.67; 95% CI, 3.00–25.03), and liver (OR, 7.31; 95% CI, 3.05–17.50). Conclusions Patients with cancer had a higher in‐hospital acute mortality for VTE than those without cancer, especially in pancreatic, biliary tract, and liver cancers.